2022
DOI: 10.1001/jamanetworkopen.2022.3596
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Neurofilament Light Chain Serum Concentrations, Physical Activity, and Cognitive Decline in Older Adults

Abstract: This cohort study uses data from the Chicago Health and Aging Project to examine associations between physical activity and cognitive decline by serum concentrations of neurofilament light (NfL) chain among older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
(77 reference statements)
0
21
0
Order By: Relevance
“…In aging research, the NfL levels have been shown to increase with normal aging [7,8]. This index has also been used in cohort and RCT studies for healthy older adults [34,35]. For example, Desai et al (2022) utilized the NfL levels to classify the participants and investigated the association between physical activity levels and cognitive decline [34].…”
Section: Discussionmentioning
confidence: 99%
“…In aging research, the NfL levels have been shown to increase with normal aging [7,8]. This index has also been used in cohort and RCT studies for healthy older adults [34,35]. For example, Desai et al (2022) utilized the NfL levels to classify the participants and investigated the association between physical activity levels and cognitive decline [34].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, physical exercise has been found to be associated with better cognitive functioning in older adults, with increased serum neurofilament concentrations [ 37 ]. Some studies investigating the effect of different kinds of physical exercises not only on cognition [ 35 , 38 ] but also on the mood and emotional states, reported beneficial effects in individuals practicing sports [ 35 , 39 ].…”
Section: Aerobic Exercise Effects On Cognitive Functions and Neural S...mentioning
confidence: 99%
“…Desai et al showed that any physical activity (vs no physical activity) was associated with slower cognitive decline in older adults when stratified by low and high neurological risk as measured by plasma levels of NfL. This observation paves the way for other biomarker studies in population-based settings that include lifestyle factors and interventions.…”
mentioning
confidence: 98%
“…The advent of blood-based biomarkers that, unlike plasma NfL and total tau, are specific for AD-related processes, such as plasma phosphorylated tau (reflecting altered tau metabolism in response to amyloid plaques), the Aβ42/40 ratio (a biomarker of amyloid plaque formation), and glial fibrillary acidic protein (marking astroglial activation), remain to be adequately evaluated in observational studies, randomized clinical trials, and community intervention settings 7. As evident in the study by Desai et al,1 blood-based biomarkers have the potential to deepen the understanding of risk factor management alongside underlying pathophysiological processes that eventually lead to dementia. This is an open access article distributed under the terms of the CC-BY License.…”
mentioning
confidence: 99%
See 1 more Smart Citation